Saint Peter and Saint Paul Archipelago barcoded: Fish diversity in the remoteness and DNA barcodes reference library for metabarcoding monitoring - Marcelo Merten Cruz; Lilian Sander Hoffmann; Thales R. O. de Freitas (Genetics and Molecular Biology, 2022)
Abstract In order to monitor the effects of anthropogenic pressures in ecosystems, molecular techniques can be used to characterize species composition. Among molecular markers capable of identifying species, the cytochrome c oxidase I (COI) is the most used. However, new possibilities of biodiversity profiling have become possible, in which molecular fragments of medium and short-length can now be analyzed in metabarcoding studies. Here, a survey of fishes from the Saint Peter and Saint Paul Archipelago was barcoded using the COI marker, which allowed the identification of 21 species. This paved the way to further investigate the fish biodiversity of the archipelago, transitioning from barcoding to metabarcoding analysis. As preparatory steps for future metabarcoding studies, the first extensive COI library of fishes listed for these islands was constructed and includes new data generated in this survey as well as previously available data, resulting in a final database with 9,183 sequences from 169 species and 63 families of fish. A new primer specifically designed for those fishes was tested in silico to amplify a region of 262 bp. The new approach should guarantee a reliable surveillance of the archipelago and can be used to generate policies that will enhance the archipelago’s protection.